The regulation of governance by the executive board and supervisory board: The case of the Maghreb countries - TOUMI, Said; KABBAJ, Ismail (Revue du contrôle, de la comptabilité et de l’audit, 2021)
In recent decades, the issue of corporate governance remains a topic of topicality, it is sensible, among other things, to protect the interests of investors from the excesses of management of leaders, in this framework, most countries of the world have developed codes of good governance practices to ensure a sound management of the company and thus to preserve the country's economy from malfunctions. The purpose of this article is to present a simple comparison between the laws governing companies with supervisory boards in the Maghreb countries (Morocco, Algeria and Tunisia). The characteristics of the management method and their impact on the company's performance are poorly studied. Management by the executive board and supervisory board is the most mentioned in the codes of governance because it allows dissociation between the power of management and the power of management control. In this research, we seek to highlight the laws that govern the supervisory boards and directory of companies in the Maghreb countries.